Working out of method of comparison of the trainy systems of sportsmen-bodybuilders - Джим [Victor Djim] Віктор Юрійович; Адаменко [Nikolaj Adamenko] Микола Іванович (Slobozhanskyi Herald of Science and Sport, 2013)
The present paper is devoted to problems of training athletes and powerlifters, bodybuilders to compete with foreign adaptation of classical methods to national realities to achieve in this way the best results. The article deals with the comparison of existing methods of training athletes. One of the main indicators of reliability methodologies used is the number of instructors (trainers) involved in the training process. In this regard, the article is relevant to solve the problem of determining the relative reliability of different types of techniques by the two groups of athletes being diferent in the number of outsiders, or, alternatively, on the basis of champions of competition. Advanced taken into account that this figure is a random variable. Formulated and solved the problem: to determine the relative effectiveness of different types of techniques methods of the theory of probability on the number of outsiders. This general formulation of the problem which allows to use its solution to any number of different training systems is combined to obtain specific numerical results.